Cloud Computing for Beginners - Database Technologies and Infrastructure as a Service - Gabrieli, Idan (Packt Publishing, 2021)
Explore the world of database technologies and join the cloud computing revolution with hands-on knowledge on DBaaS and IaaS models About This Video Learn the technical concept, market use cases, advantages, and disadvantages of the DBaaS model Learn the technical concept, market use cases, advantages, and disadvantages of the IaaS model Review key terms in cloud computing to establish a clear understanding In Detail Over the last couple of years, many business companies decided to use more and more cloud services as part of their digital transformation, and you already know data is the new gold. Therefore, this course is predominantly divided into two important parts: database technologies and infrastructure as a service. The first part is about databases technologies and, even more specifically, how such technologies are offered as cloud database services (DBaaS) by leading public cloud providers--Azure, AWS, and GCP. We will learn the technical concept, market use cases, advantages, and disadvantages of each database technology while following its evolution path. The next part is about the IaaS model. The IaaS model provided by large cloud providers is helping companies transform their private IT infrastructure into a utility service. As a first step, you will review the key terms in cloud computing to establish a clear understanding of the big picture, and then we will zoom in on the IaaS model. The look at building blocks, what are the typical use cases, advantages as well as disadvantages, pricing models, and more. By the end of this course, you will be able to select the right database technology for a specific use case to dramatically affect any aspect of an application and learn about the IaaS model of cloud computing. Who this book is for This course is designed for the software developers, IT professionals, product/project/marketing managers who wish to reduce the footprint of enterprise applications sitting in private data centers and leverage the capabilities in a public cloud environment. Solution architects, technical advisors, telecom experts, and security professionals can also get benefit from this course. You don't need to have prior knowledge of cloud computing concepts.